2009
DOI: 10.1590/s0073-47212009000100013
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição geográfica potencial de espécies americanas do caranguejo "violinista" (Uca spp.) (Crustacea, Decapoda) com base em modelagem de nicho ecológico

Abstract: ABSTRACT. Potential geographical distribution of American species of "fiddler crab" (Uca spp.) (Crustacea, Decapoda) based on ecological niche model. The genus Uca Leach, 1814 (fiddler-crabs) is a well-know group characterized by a marked sexual dimorphism. Worldwide, there are 97 species of fiddler crabs described. Here, we predicted the potential geographical distribution of four species of this genus (Uca maracoani Latreille, 1802-1803, U. uruguayensis Nobili, 1901, U. panacea Novak & Salmon, 1974 e U. moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…Despite the high frequency of papers using GARP, recent comparative work has suggested that the Maxent models provide better results (Phillips et al, 2004;Elith et al, 2006;Phillips et al, 2006) and that they are more computationally efficient. However, Nabout et al, (2009) recorded higher AUC values for GARP when compared to Maxent when modelling the potential distributions of American fiddler crabs. Moreover, other papers support the importance of employing different modelling techniques.…”
Section: Ensemble Forecasting and Distribution Modelingmentioning
confidence: 88%
“…Despite the high frequency of papers using GARP, recent comparative work has suggested that the Maxent models provide better results (Phillips et al, 2004;Elith et al, 2006;Phillips et al, 2006) and that they are more computationally efficient. However, Nabout et al, (2009) recorded higher AUC values for GARP when compared to Maxent when modelling the potential distributions of American fiddler crabs. Moreover, other papers support the importance of employing different modelling techniques.…”
Section: Ensemble Forecasting and Distribution Modelingmentioning
confidence: 88%
“…Theses papers of Brazilian journal have focused mainly on issues such as ecology (e.g. NABOUT et al, 2009), morphology (e.g. BEZERRA & COELHO, 2009, and population structure (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…All fiddler crabs have until recently been considered to be in a unique genus (Uca Leach, 1814), composed of 97 widely distributed species (Crane, 1975;Rosenberg, 2001), but current reorganization has separated them into different genera based on phylogenetic relationships (Shih et al, 2016). Although each species shows a varied distribution range, in many areas theses ranges overlap and co-occurrence is common (Crane, 1975;Nabout et al, 2009;Thurman et al, 2013). Factors affecting large-scales patterns are related to larval survival during dispersal and settlement, such as water current, wind pattern and temperature change with latitudinal gradients (Bogazzi et al, 2001;Nabout et al, 2009;Wieman et al, 2014).…”
mentioning
confidence: 99%
“…Although each species shows a varied distribution range, in many areas theses ranges overlap and co-occurrence is common (Crane, 1975;Nabout et al, 2009;Thurman et al, 2013). Factors affecting large-scales patterns are related to larval survival during dispersal and settlement, such as water current, wind pattern and temperature change with latitudinal gradients (Bogazzi et al, 2001;Nabout et al, 2009;Wieman et al, 2014). On a local scale, variables such as sediment grain size, tidal level, vegetation cover and salinity influence species occurrence and distribution (Thurman, 1987;Thurman et al, 2013;Mohktari et al, 2015;Checon & Costa, 2017).…”
mentioning
confidence: 99%